Robust fuzzy controller development for a PEM fuel cell system. (16th February 2009) - Thanapalan, K.K.T.; Liu, G.P.; Williams, J.G.; Rees, D.
A polymer electrolyte membrane (PEM) fuel cell system model that is suitable for control study is presented in this paper. The PEM mathematical model is then used for the controller development to improve system performance. Within the university research facilities, there is available a PEM fuel cell test station (PEM-FCT), so the PEM-FCT is used for the modelling and controller study. A fuzzy set-point weighted PID controller is designed to improve the performance of the fuel cell system. The underlying idea of our controller design is to use a fuzzy based system to support the operation of a PID controller. The new control strategy is implemented on a PC based computer model of the FCT system and simulated. The results indicate that the control strategy has improved the system performance significantly. Thus, the new control strategy is implemented on PEM-FCT. Comparison made between the simulation model response and experimental results from the real FCT system using the same controller which shows performance enhancements, compared with the existing closed loop controller based on stoichiometry value updates to the flow controllers.